Optimalisasi Pengelolaan UKM Madu dalam Mensejahterakan Masyarakat Desa Cibodas Kabupaten Majalengka - Nita Hernita; Wulan Riyadi; Engkun Kurnadi; Melia Wida Rahmayani (CV. Multi Kreasi Media, 2022)
The Honey UKM in Cibodas Village, Majalengka District, Majalengka Regency which is used as a partner in this PKM has problems that are of special concern to find solutions. The problems that exist include partners who are still low in entrepreneurial spirit, do not have permanent employees who can maintain product quality, so that the honey produced is still not optimal, partners do not have extensive knowledge of recording and bookkeeping, so that the financial statements produced are not in accordance with accounting standards, partners do not yet have a brand for the product or the name of the partner itself. The production equipment used is not adequate, only uses 2 boards for honey-producing beekeeping, does not yet have a PIRT and business license, both SIUP and SIUPL, Marketing is carried out only based on direct orders and has not touched the local or online market. The product does not yet have a halal label and nutritional value information so that the product cannot enter the minimarket. Based on the findings regarding the problem, the priority is to find solutions to problems in improving various aspects. Among them are managerial aspects related to finance and human resources in an effort to increase the capacity of managers. Furthermore, the technological aspects in an effort to improve product quality. Changes in marketing aspects towards digitalization and broader marketing aspects by obtaining halal labels and information on nutritional values. The specific goals and targets in this community service are to assist Madu UKM in improving product quality and competitiveness through the use of technology and managerial management to be able to compete in the new normal era. The method used in an effort to implement the solution above is holding training for strengthening SME managers, partner bookkeeping every 2 weeks, training on beekeeping in producing quality honey, creating a management information system, creating social media, joining various e-commerce sites, making product information website, participating in culinary exhibitions and bazaars, facilitating the inclusion of halal logos and information on nutritional values ​​in packaging. The output produced is in the form of publications in the form of service journals and intellectual property rights.